2013
DOI: 10.1063/1.4842117
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional elastic constitutive relations of aligned carbon nanotube architectures

Abstract: Tailorable anisotropic intrinsic and scale-dependent properties of carbon nanotubes (CNTs) make them attractive elements in next-generation advanced materials. However, in order to model and predict the behavior of CNTs in macroscopic architectures, mechanical constitutive relations must be evaluated. This study presents the full stiffness tensor for aligned CNT-reinforced polymers as a function of the CNT packing (up to ∼ 20 vol. %), revealing noticeable anisotropy. Finite element models reveal that the usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 40 publications
5
50
0
Order By: Relevance
“…These uncertainties in Γ min at V f ∼ 5% were estimated at ∼ ±10 − 15%, which lead to about the same order of magnitude of uncertainty in accessible porosity (see Figure 2c), as observed in the experimental data (see Figure 3b). Also, because previous studies on the capillary-assisted wetting of CNT arrays of varying V f with epoxy resins, which are less sensitive to moisture than phenolics, did not observe such an impact on infusion yield, [79][80][81][82] further studies on the interaction of the physisorbed water layers with introduced polymer species of varying chemistries is necessary. …”
mentioning
confidence: 99%
“…These uncertainties in Γ min at V f ∼ 5% were estimated at ∼ ±10 − 15%, which lead to about the same order of magnitude of uncertainty in accessible porosity (see Figure 2c), as observed in the experimental data (see Figure 3b). Also, because previous studies on the capillary-assisted wetting of CNT arrays of varying V f with epoxy resins, which are less sensitive to moisture than phenolics, did not observe such an impact on infusion yield, [79][80][81][82] further studies on the interaction of the physisorbed water layers with introduced polymer species of varying chemistries is necessary. …”
mentioning
confidence: 99%
“…12 To utilize the exceptional and highly anisotropic intrinsic properties of NFs in material solutions, many recent studied focused on the use of aligned NF arrays, especially aligned carbon nanotubes (A-CNTs), in nanocomposite structures, specifically aligned CNT polymer matrix nanocomposites (A-PNCs). [18][19][20][21][22][23][24][25][26][27][28] However, the properties reported by these previous works did not live up to the behavior predicted using current theoretical frameworks. 12 Some of the main reasons why existing models cannot accurately predict the behavior of A-CNTs architectures, such as A-CNT arrays, are the various CNT morphology and proximity effects, 13,14,18,29 which can strongly impact properties, 27,30,31 but are not well understood and cannot be adequately described in current-generation theoretical frameworks.…”
mentioning
confidence: 72%
“…Also, previous work on A-PNCs has shown that CNT waviness could lead to composite moduli that are > 10× lower than the ones predicted by rule of mixtures analysis of collimated CNTs, 26,34 and that the waviness of the CNTs can be reduced by CNT packing proximity, normally quantified by an increase in the CNT volume fraction (V f ). 26,58 However, current-generation theoretical and numerical models cannot account for an evolving waviness ratio (w), and can only describe the CNT waviness using simple functional forms, e.g. sinusoidal or helical functional forms.…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an A-PNC is a representative volume element in such nanoengineered FRP composites. Here, we focus on the prediction of A-PNC elastic properties based on constituent properties using a combined molecular dynamics and finite-element approach, looking towards experiment-model correlation with regard to experimental work [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%